Characterization and Antioxidant Activity Edible Film of Durian (Durio zibethinus) Seed Starch with the Addition of Soursop (Annona muricata L.) Leaf - Yuni Fatisa; Nadya Agustin (Indonesian Journal of Chemical Science and Technology (IJCST), 2018)
Edible film is one of the environmentally friendly packaging materials and not harmful to health because it is made up of natural ingredients such as proteins, lipids, and polysaccharides. In addition to environmentally friendly, the development of edible film on food packaging can provide better product quality, as it is made from natural ingredients that contain various natural chemical compounds that are beneficial and can be directly consumed. In this study prepared edible film derived from durian seed starch with the addition of soursop leaf extract. This research aimed at knowing the physical and chemical characteristics, and antioxidant activity of  the edible film. The type of research used is experiment methods. The results showed that the best research findings of the edible film were on the addition of 2 g soursop leaf extract and the physical characteristic was transmission of water vapor that was 1.70 g/m2. 24 hours, the chemical characteristics were water content that was 17.33% and activity of antioxidant that was 1.5875 mg/mL.